Suzel Ana Reily (ed.), The Musical Human: Rethinking John Blacking’s Ethnomusicology in the Twenty-First Century (2006) - Smith, Thérèse (Journal of the Society for Musicology in Ireland, 2007)
A review of Suzel Ana Reily (ed.), The Musical Human: Rethinking John Blacking’s Ethnomusicology in the Twenty-First Century (Aldershot: Ashgate, 2006), ISBN: 0-7546-5138-X, 234 pp, £47.50/$94.95.